Keabsahan Transaksi E-Commerce Dalam Pembuatan Akta Perspektif Cyber Notary Dengan Menggunakan Digital Signature - Darmawan, Komang Dicky; Dananjaya, Nyoman Satyayudha (Acta Comitas : Jurnal Hukum Kenotariatan, 2022)
This research aims to examine and analyse whether making a notary deed using the cyber notary method is legal under many legislative laws and how to settle disputes if the notary deed is created via the cyber notary method. This research uses normative legal research methods by examining secondary data like library resources and uses a conceptual approach. Normative legal research applies primary, secondary, and tertiary legal information. The descriptive-qualitative research method was applied in this research. Making a relaas from the Cyber Notary’s perspective is permitted since the meeting procedure at the GMS via video conference is still legal, and the notary who produces the meeting’s minutes must fulfil the GMS standards. However, using the Cyber Notary perspective to make the partij deed is invalid since the notary is required to understand the detail of making deed by hearing and seeing the signing that occurred between the parties by the provisions of Article 16 paragraph (1) letter m UUJN. Electronic signature-enabled E-commerce transactions are legal if they have been registered with the Certification Authority. Nevertheless, the use of a digital signature in an Authentic Deed is prohibited under the UUJN, UU ITE, and PP PSTE. Therefore, to resolve Electronic signature-enabled E-commerce transactions usually result in losses for the parties to the agreement, followed by dispute resolution through arbitration in form of a peace deed. Arbitration is thought being more convenient than going via the courts, which takes a lot of time, money, and energy.